ANALISIS MINAT BELAJAR FISIKA PESERTA DIDIK TERHADAP PEMBELAJARAN DARING - Ana Dhiqfaini Sultan; Nurfadilah Nurfadilah; Andi Arie Andriani (Institut Pendidikan Tapanuli Selatan, 2024)
This simple experiment is entitled analysis of students' interest in learning physics towards online learning which aims to analyze students' learning interest in online learning in physics lessons. This type of research is a qualitative research with a case study approach. The research sample was 136 students of SMA Negeri 15 Wajo who were randomly selected from the seven classes X, XI and XII MIPA. The results showed that the lowest percentage of the indicator of interest in learning physics was the attention of students to learning physics online, while the highest percentage was the indicator of interest in learning, namely the involvement of students in learning physics online. Based on the results of the study, it can be concluded that the learning interest of students at the beginning of online physics learning can be categorized as good and has considerable involvement during learning, but over time, students' interest in learning physics online decreases due to boredom and boredom. begin to be felt by students